2010
DOI: 10.1002/cphc.201000244
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation in Wurtzite/Zinc‐Blende Heterojunction GaN Nanowires

Abstract: The electronic properties of wurtzite/zinc-blende (WZ/ZB) heterojunction GaN are investigated using first-principles methods. A small component of ZB stacking formed along the growth direction in the WZ GaN nanowires does not show a significant effect on the electronic property, whereas a charge separation of electrons and holes occurs along the directions perpendicular to the growth direction in the ZB stacking. The later case provides an efficient way to separate the charge through controlling crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Therefore, these structures clearly indicate the construction of a type I heterojunction [34][35][36] in which quantum confinement can be achieved, offering an effective way to obtain GeNR-based quantum well devices. The corresponding schematic description of this type I heterojunction is shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, these structures clearly indicate the construction of a type I heterojunction [34][35][36] in which quantum confinement can be achieved, offering an effective way to obtain GeNR-based quantum well devices. The corresponding schematic description of this type I heterojunction is shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, it is believed that the large distribution and atomic level interconnection of twin-induced heterophase junctions in Cd 1−x Zn x S NCs lead to the vectorial interfacial transfer of photoexcited charge carriers between the ZB and WZ phase. 49,51 L-Cysteine molecules can bind to Cd 1−x Zn x S surfaces by coordination through the sulfur atoms and metal cations, as confirmed by IR analysis (Figure S6). The L-Cysteine ligand protects nanocrystals from oxidation and traps holes from NCs at the interface.…”
Section: Resultsmentioning
confidence: 74%
“…Furthermore, it was reported that the WZ phase occupies a CB and VB position higher than that of its ZB counterpart; consequently, the photoinduced electrons transfer from the CB of WZ to the CB of ZB, while holes migrate from the VB of ZB to the VB of WZ, achieving highly effective separation of electron–hole pairs. Moreover, it is believed that the large distribution and atomic level interconnection of twin-induced heterophase junctions in Cd 1– x Zn x S NCs lead to the vectorial interfacial transfer of photoexcited charge carriers between the ZB and WZ phase. , l -Cysteine molecules can bind to Cd 1– x Zn x S surfaces by coordination through the sulfur atoms and metal cations, as confirmed by IR analysis (Figure S6). The l -Cysteine ligand protects nanocrystals from oxidation and traps holes from NCs at the interface.…”
Section: Resultsmentioning
confidence: 85%
“…Surprisingly, the AlN/GaN superlattice nanowire has the lowest work function, which may be due to a tiny internal field generated in sublayers. This internal field are also found form some heterojunction and superlattice structures 27,28 . The larger the composition difference between the sublayers, the higher the field intensity, and electrons inside nanowire are more easily migrated to the surface to escape, so the probability of the escape of the internal photoelectrons is increased, that is, the work function is reduced.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, Figure 4 shows structures. 27,28 The larger the composition difference between the sublayers, the higher the field intensity, and electrons inside nanowire are more easily migrated to the surface to escape, so the probability of the escape of the internal photoelectrons is increased, that is, the work function is reduced. The above results indicate that the field intensity is effectively controlled by changing composition of the superlattice nanowires to improve the emission performance of the photocathode.…”
Section: Electronic Properties Of Superlattice Nanowiresmentioning
confidence: 99%